Investigations in medieval stained glass : materials, methods, and expressions - Pastan, Elizabeth Carson; Pastan, Elizabeth Carson; Kurmann-Schwarz, Brigitte; Kurmann-Schwarz, Brigitte (Reading medieval sources, 2019)
The Medieval Glazier at Work - Sarah Brown -- A Matter of Matter : Transparent - Translucent - Diaphanum in the Medium of Stained Glass / Wojciech Balus -- Performative Interaction of Liturgy and Light through the Medium of Painted Glass / Madeline H. Caviness -- Regarding the Early Rose Window / Elizabeth Carson Pastan -- Medieval Textual Sources on Stained Glass : from Theophilus to the Monk of Zagan / Brigitte Kurmann-Schwarz -- The Beginnings of Stained-Glass Collecting in Germany / Uwe Gast.